Lumbosacral plexopathy following alcohol-induced rhabdomyolysis: a case report - Seliverstova, E. G.; Sinkin, M. V.; Grin, A. A. (Frontiers in Musculoskeletal Disorders, 2025)
ObjectiveWe present a rare case of lumbosacral plexopathy secondary to alcohol-induced rhabdomyolysis.Case descriptionA 58-year-old male patient was admitted to the intensive care unit (ICU). He reported a sensation of weakness in both legs and a tingling sensation in his feet upon awakening post binge drinking. Magnetic resonance imaging (MRI) of the thoracic and lumbar spine did not reveal any intraspinal abnormalities. However, an MRI showed lesions with abnormal intensities in both paraspinal muscles. Serum creatine phosphokinase level was markedly elevated. A diagnosis of lumbosacral plexopathy following alcohol-induced rhabdomyolysis was determined by clinical findings, MRI data and an electrophysiological evaluation. Upon discharge, lower limb strength was significantly improved.DiscussionIn severe rhabdomyolysis, the resulting kidney injury and electrolyte imbalances can lead to systemic complications, including peripheral neuropathy or plexopathy. The exact mechanisms by which this occurs are not fully understood, however it is believed that the accumulation of toxic substances, electrolyte imbalances, and metabolic disturbances can contribute to nerve damage and dysfunction. Therefore, lumbosacral plexopathy should be included in the differential diagnosis of such cases, presenting with sudden leg weakness.